A Scoping Review on Psychological Capital and Its Impact on Academic Outcomes (Journal of Contemporary Educational Policies and Practices, 2025)
Psychological Capital (PsyCap) is an emerging construct in positive psychology that has garnered significant attention in organizational and academic contexts. While extensively studied in workplace settings, PsyCap’s relevance in academic environments is increasingly recognized, as it influences students’ motivation, engagement, and academic success. This literature review synthesizes the conceptual framework of PsyCap, its components, antecedents, and consequences, and examines its impact on academic outcomes through a review of related empirical studies. Studies in the Scopus database were searched, and a total of 16 studies were included in this review. Drawing on studies employing cross-sectional and longitudinal designs, the review highlights PsyCap’s function as a mediator, direct predictor, and occasional moderator in linking psychosocial factors (e.g., teacher-student relationships, parent-child relationships, positive emotions, school climate, personality traits) to academic outcomes, typically measured by grade point average (GPA) or cumulative grade point average (CGPA). Grounded in theoretical frameworks such as Self-Determination Theory, Broaden-and-Build Theory, and Conservation of Resources Theory, the findings confirm PsyCap’s capacity to translate supportive environments into enhanced performance while mitigating challenges like stress and burnout. Theoretical implications extend PsyCap frameworks to educational contexts, while practical recommendations advocate for PsyCap-focused interventions, supportive relationships, and positive school climates. Policy implications emphasize curriculum integration and teacher training. Future research should prioritize longitudinal designs, diverse samples, and multi-method approaches to enhance causal inferences and applicability, reinforcing PsyCap’s transformative potential in optimizing student success.
Keywords: PsyCap; literature review; PsyCap’s impacts; academic achievement; PsyCap as a mediator; direct predictor; occasional moderator